2019
DOI: 10.1186/s12955-019-1218-6
|View full text |Cite
|
Sign up to set email alerts
|

Religious practices and changes in health-related quality of life after hospital discharge for an acute coronary syndrome

Abstract: Background Religious beliefs and practices influence coping mechanisms and quality of life in patients with various chronic illnesses. However, little is known about the influence of religious practices on changes in health-related quality of life (HRQOL) among hospital survivors of an acute coronary syndrome (ACS). The present study examined the association between several items assessing religiosity and clinically meaningful changes in HRQOL between 1 and 6 months after hospital discharge for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
1
4
0
1
Order By: Relevance
“…There is a growing body of research indicating that negative feelings toward the divine or religious community are often linked with lower levels of life satisfaction (Abu-Raiya et al 2018;Szcześniak et al 2019). Zarzycka and Zietek (2018) found that divine, demonic, interpersonal, moral, doubt, and ultimate meaning domains of religious struggle correlated negatively with life satisfaction, confirming some previous studies conducted among various groups of patients (Abu et al 2019;Manning-Walsh 2005;Park et al 2011;Ursaru et al 2014). Since life satisfaction is a broad concept (Loewe et al 2014) and dissatisfaction with life manifests itself in some poor health outcomes (Gigantesco et al 2019), it is valuable to investigate how religious struggle relates to some indicators of life satisfaction.…”
Section: Religious Struggle and Life Satisfactionsupporting
confidence: 68%
“…There is a growing body of research indicating that negative feelings toward the divine or religious community are often linked with lower levels of life satisfaction (Abu-Raiya et al 2018;Szcześniak et al 2019). Zarzycka and Zietek (2018) found that divine, demonic, interpersonal, moral, doubt, and ultimate meaning domains of religious struggle correlated negatively with life satisfaction, confirming some previous studies conducted among various groups of patients (Abu et al 2019;Manning-Walsh 2005;Park et al 2011;Ursaru et al 2014). Since life satisfaction is a broad concept (Loewe et al 2014) and dissatisfaction with life manifests itself in some poor health outcomes (Gigantesco et al 2019), it is valuable to investigate how religious struggle relates to some indicators of life satisfaction.…”
Section: Religious Struggle and Life Satisfactionsupporting
confidence: 68%
“…The use of acceptance and religion as a coping strategy has been associated with better health-related quality of life. 41 , 42 Denial was the least endorsed coping strategy for non-Hispanic, White persons and substance use was the least endorsed coping strategy for Black respondents. These findings are in line with a previous study investigating stress during the pandemic.…”
Section: Discussionmentioning
confidence: 94%
“…95 Os pacientes que oraram por sua saúde e os que estavam cientes das intercessões feitas por terceiros em intenção à sua saúde experimentaram melhorias na qualidade de vida relacionadas à saúde ao longo do tempo. 96 No Multiethnic Study of Atherosclerosis (MESA), não foram observados padrões consistentes de associação entre as medidas de religiosidade e presença/extensão de DCV subclínica na avaliação basal ou incidentes dela ao longo de 4 anos. 97 Com relação à associação entre espiritualidade/ religiosidade e fatores de risco CV, os achados são discordantes.…”
Section: Espiritualidade E Eventos Cardiovasculares Relevantesunclassified